Perception of some riverine people, from the islands of the municipality of Abaetetuba-PA, about intestinal parasites (Research, Society and Development, 2022)
Objectives: To know and describe some perceptions, practices and evaluative aspects of people living along the Ajuai and Capim rivers, about cases of intestinal parasites, the main difficulties in accessing health care and the need for health education in these riverside locations. Methodology: This is an ethnographic study, developed in the riverside communities of the Ajuai and Capim rivers, in the municipality of Abaetetuba (Pará/Brazil), carried out through interviews with riverside people about the socioeconomic profile, forms of health treatment and common diseases affected in the communities, from June 2017 to July 2018. Results: The study showed that the interviewed residents report the existence of a community exposed to infections by enteroparasites, mainly due to the lack of basic sanitation and that makes use of practices care, such as the use of plants, because due to the distance from the Municipality, they do not have access to the medicines they need to fight the intestinal parasites with which they are affected. Conclusion: The findings of this study indicate the constant need for sanitary and health education actions for the population and, on the other hand, knowledge of health professionals about concepts and attitudes of certain populations in face of different situations in order to optimize the promotion and health prevention.